2017
DOI: 10.1016/s2095-3119(16)61585-x
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS) concentrations in the South Korean agricultural environment: A national survey

Abstract: Research on the occurrence of perfluorochemicals (PFCs) such as perfluorooctanesulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) in the agricultural environment is lacking, in spite of their potential risk via food chain transfer from aquatic and soil-plant systems to animals and/or humans. In the present study, for the first time, soil and water samples collected from 243 different agricultural sites adjacent to waste water treatment plants (WWTPs) belonging to 81 cities and 5 provinces with different le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The sample preparation for the extraction of soil was followed the reported method by Choi et al (2017). Briefly, the soil samples were dried at the room temperature under fume hood and passed through 2 mm sieve.…”
Section: Sample Preparation For the Analysis Of Pfoa And Pfos In Soil And Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample preparation for the extraction of soil was followed the reported method by Choi et al (2017). Briefly, the soil samples were dried at the room temperature under fume hood and passed through 2 mm sieve.…”
Section: Sample Preparation For the Analysis Of Pfoa And Pfos In Soil And Cropsmentioning
confidence: 99%
“…However, being highly persistent, PFAAs are frequently detected even in remote regions (Guo et al, 2016;Jian et al, 2017;Perez et al, 2014;Sungur, 2018). Recent research has indicated that PFAAs are present in sub part-perbillion (ppb) concentrations of 88.7% in farmland soil in Korea (Choi et al, 2017). Furthermore, for humans, the major sources of exposure to PFAAs are the PFOA and PFOS residues present in food, particularly protein-rich foods, such as meat, dairy, and fish (Brambilla et al, 2015;Ghisi et al, 2019;Heo et al, 2014;Xiang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The analytical soil sample preparation was followed by Choi et al [6]. Briefly, 1% aqueous acetic acid (10 mL) was added to 1.0 g air-dried soil sample, then it was shaken for 30 min, sonicated for 15 min and centrifuged at 3000 rpm.…”
Section: Analytical Sample Preparation For Residual Pfaas In Soilmentioning
confidence: 99%
“…Recently, the residues of PFOA and PFOS were surveyed in agricultural environment by Choi et al [6] and most of the residue distribution of the sum of PFOA and PFOS were reported below 0.05 µg L −1 (92%) in the irrigation water and below 1.0 µg kg −1 (88%) in the farmland soil. In addition, some of the PFAAs residue surveys for food in Korea were investigated by a few researchers [13,27].…”
Section: Introductionmentioning
confidence: 99%
“…PFOA and PFOS are two PFASs most commonly used in the industry and the most commonly determined PFASs in living organisms and the environment. Their prevalence and long-distance migration are evidenced by data regarding their presence in soil [ 110 , 111 ]; air [ 112 ], including Arctic air [ 113 ]; groundwater [ 114 ]; deposits [ 115 ]; snow in regions, including the Antarctic [ 116 ]; and rain water and surface water [ 117 ]. Due to their amphophilic properties, PFASs relatively easily migrate to the aquatic environment [ 65 ].…”
Section: Pfass In Environmentmentioning
confidence: 99%